The Dharma bum's guide to western literature finding nirvana in the classics - Sluyter, Dean (New World Library, 2022)
"A meditation instructor and former English teacher shows how the great classics of Western literature illustrate the essential concepts of Eastern philosophy. The discussion includes works by authors such as John Keats, William Shakespeare, Virginia Woolf, Frederick Douglass, and many others"--Provided by publisher.